Acrylate emulsion for ceramic tile back adhesive as well as preparation method and application of acrylate emulsion

By designing the core-shell structure and particle structure of the ceramic tile back glue and adjusting the amount of thickener, the problem that existing products are difficult to meet high initial viscosity and high bond strength at the same time under low solids conditions, achieving free regulation of emulsion viscosity and improving product performance.

CN119798550APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510001368.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing ceramic tile adhesive backing products are difficult to meet the high initial viscosity and high bond strength at the same time under low solids conditions, and the viscosity is difficult to control freely, which cannot meet the needs of different construction sites.

Method used

By designing the soft and hard monomer ratio of the core-shell structure, the cohesion of the product is improved, combined with the particle structure design, the amount of thickener is adjusted to freely regulate the emulsion viscosity, ensuring that the product has stable high viscosity and excellent initial viscosity and bonding strength under low solids conditions.

Benefits of technology

The high initial viscosity and high bond strength of ceramic tile backing glue are achieved, and the emulsion viscosity can be freely regulated, meeting the needs of different construction sites and improving the comprehensive performance and competitiveness of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225304940000051
    Figure BDA0005225304940000051
  • Figure BDA0005225304940000061
    Figure BDA0005225304940000061
  • Figure BDA0005225304940000131
    Figure BDA0005225304940000131
Patent Text Reader

Abstract

The invention discloses an acrylate emulsion for a ceramic tile back adhesive and a preparation method and application thereof, the acrylate emulsion is polymerized by adopting a core-shell emulsion polymerization technology, and a core layer and a shell layer in core-shell emulsion particles respectively account for 65%-95% and 5%-35% of the total mass of a polymer. The acrylate emulsion has the advantages of large particle size, milk white color, stable and freely controllable emulsion viscosity under the conditions of low solid content and moderate particle size, stable high emulsion viscosity, facilitation of construction, low solid content, effective reduction of the formula cost, and improvement of the product competitiveness. The ceramic tile back adhesive prepared from the adhesive has high initial viscosity and high bonding strength, can still keep high bonding strength after being soaked in water, is non-toxic and environment-friendly, is convenient to construct, and is an ideal bonding material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to an acrylic emulsion for tile back glue, a preparation method and application thereof. Background Art

[0002] With the rapid development of building interior and exterior wall finishes, a large number of low or even zero water absorption and large-sized finishing materials have emerged, such as ceramic thin plate tiles, vitrified tiles, polished tiles, microcrystalline stones, antique tiles, artificial marble, etc. The paving materials have also developed from cement mortar to tile adhesives and tile adhesives. As the water absorption rate of tiles becomes lower and lower, the pasting surface becomes smoother and denser, and the traditional paving can no longer meet the bonding requirements. In particular, vitrified tiles and polished tiles have high material strength, are sensitive to temperature changes, and the temperature difference is not synchronized. Different from the thermal expansion coefficient of cement, large-sized tiles will have temperature stress after paving. Seasonal temperature oscillations will cause the bonding strength to decrease, destroy the bonding strength between the brick body and the substrate, and cause hollowing between the tiles and the structural layer due to poor bonding and bonding. Cement mortar is a rigid material with good durability but low bonding strength, and cannot resist shedding caused by thermal expansion and contraction or wet expansion and dry shrinkage. The laying of this type of finishing material requires that the tile adhesive has strong adhesion and sufficient flexibility to withstand the damage caused by climate change and the slight vibration of high-rise buildings. For polished tiles, vitrified tiles, and architectural thin tiles with low water absorption and large sizes, C2-level tile adhesives are recommended, but the overall laying cost is high. In addition, most domestic tile adhesive manufacturers have been manufacturing products according to the C1 standard, and some cannot even meet the C1 standard, which leads to hollowing and falling off of tiles with low water absorption.

[0003] Tile adhesive, as a new type of tile paving material applied to the back of tiles, can not only effectively reduce the surface tension of the tile surface, but also improve the bonding ability between the tile and the cement mortar layer, effectively solving the problems of hollowing and tile falling off, and extending the service life of the tiles.

[0004] There are many types of single-component tile adhesives commonly used in the market, but they all have the problem of not being able to take into account both high initial adhesion and high bonding strength characteristics. For example, the tile adhesive of the modified pressure-sensitive adhesive system has a high initial adhesion, but this type of adhesive often has disadvantages such as low bonding strength, poor water resistance, and soft coating in actual use. It also has low cohesion and poor impact resistance when applied on vitrified tiles. The existing high-bonding strength tile adhesive has a general initial adhesion, and due to its rigidity, it has a poor anti-vibration effect, and often has a poor brick-breaking effect. After the tiles are laid, if vibration is generated by drilling holes during decoration, it is easy for the tiles to fall off.

[0005] At present, some tile adhesive products with medium initial tack and bonding strength are also launched on the market. However, due to the characteristics of acrylic resin being hot-sticky and cold-brittle, it is still rare to find acrylic single-component adhesive products with both high initial tack and bonding strength on the market. If the glass transition temperature of acrylic emulsion is ≤-40℃, the rigidity of the macromolecular chain is insufficient, and it is difficult for the tile adhesive to achieve high bonding strength; if the glass transition temperature is increased, the bonding strength of the tile adhesive will increase, but the initial tack will decrease, which makes it difficult for the tile adhesive to have both high initial tack and high bonding strength.

[0006] In addition, in order to facilitate construction, the emulsions used for tile backing glue on the market currently require a certain viscosity. To ensure the viscosity of the product, most of the existing products are achieved by increasing the solid content of the product, which increases the cost of the product. If the viscosity of the product is to be increased by adding a thickener, the product is often accompanied by unstable viscosity, which makes it difficult for the acrylic emulsion used for tile backing glue to maintain a stable high viscosity under low solid content conditions.

[0007] In the prior art, CN202010047675 discloses an environmentally friendly versatile organic silicone acrylic modified copolymer emulsion for tile backing adhesive. The acrylic acid prepared by this method has good bonding strength, water resistance, aging resistance and other properties, but the acrylic emulsion prepared by this method has the disadvantages of insufficient initial viscosity and difficult viscosity control.

[0008] CN202110407853 discloses a method for preparing an acrylic high initial viscosity and high strength adhesive latex and its application. The acrylic emulsion prepared by this method has good initial viscosity and bonding strength, but this method still has the disadvantages of high solid content and difficulty in maintaining stable high viscosity at low solid content.

[0009] At present, with the decoration direction and the market demand for cost requirements, the emulsion for tile backing glue is required to have a lower solid content (such as 46%), a moderate particle size (about 200nm), a stable emulsion viscosity and can be freely adjusted. The tile backing glue prepared by it still has high initial viscosity and high bonding strength, thereby reducing the formula cost and improving product competitiveness. Summary of the invention

[0010] In view of this, the main purpose of the present invention is to provide an acrylic emulsion for tile adhesive to solve the problem that it is difficult to simultaneously meet the requirements of good initial adhesion and bonding strength under low solid content conditions in the prior art, and the viscosity is difficult to freely adjust. The acrylic emulsion for tile adhesive of the present invention has low solid content, moderate particle size, stable and freely adjustable emulsion viscosity, excellent initial adhesion and bonding strength, and improves the comprehensive performance of the tile adhesive.

[0011] Another object of the present invention is to provide a method for preparing the acrylic emulsion for tile back glue.

[0012] Another object of the present invention is to provide the application of the acrylic emulsion for tile back glue.

[0013] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0014] An acrylic emulsion for tile adhesive, comprising the following components in parts by mass or prepared by core-shell emulsion polymerization of raw materials consisting of the following components in parts by mass:

[0015] (1) 60-120 parts by weight, preferably 80-100 parts by weight of hard monomer;

[0016] (2) 300-450 parts by weight of soft monomer, preferably 350-420 parts by weight;

[0017] (3) 5-20 parts by weight, preferably 7-18 parts by weight, of an emulsifier;

[0018] (4) 0.6-3 parts by weight, preferably 0.9-2.6 parts by weight, of a pre-emulsion auxiliary agent;

[0019] (5) 2-8 parts by weight, preferably 3-7 parts by weight, of an oxidizing agent;

[0020] (6) 0.4-2 parts by weight, preferably 0.5-1.5 parts by weight of a reducing agent;

[0021] (7) adding 5-15 parts by weight, preferably 7-13 parts by weight, of auxiliary agents;

[0022] (8) 400-600 parts by mass, preferably 450-550 parts by mass of water;

[0023] In the scheme of the present invention, the core layer and the shell layer of the latex particles of the acrylic emulsion for tile adhesive respectively account for 65%-95% and 5%-35% of the total mass of the polymer.

[0024] In the scheme of the present invention, the hard monomer of component (1) can be any one or more combinations of butyl methacrylate, acrylamide, methyl methacrylate, styrene, acrylic acid, and methacrylic acid. Preferably, the hard monomer is selected from a combination of acid monomers containing acrylic acid and / or methacrylic acid; more preferably, the acid monomer accounts for 2-8% of the total weight of all monomers. All monomers include hard monomers and soft monomers.

[0025] In the scheme of the present invention, the soft monomer of component (2) can be any one or more of allyl methacrylate, isooctyl acrylate, butyl acrylate and ethyl acrylate.

[0026] In the scheme of the present invention, the emulsifier of component (3) can be any one or more combinations of COPS-1, sodium sulfate of tridecyl alcohol polyoxyethylene ether, sodium salt of sulfonated diphenyl ether tetrapropylene derivative, polyoxyethylene polystyrene phenol ether, sodium allyl ether hydroxypropyl sulfonate, sodium dodecyl sulfate, and sodium p-styrene sulfonate.

[0027] In the scheme of the present invention, the pre-emulsion auxiliary agent of component (4) can be at least any one of a chain transfer agent, a buffer, and a coupling agent; preferably, the chain transfer agent is any one of n-dodecyl mercaptan and butyl mercapto; the buffer is any one of sodium bicarbonate, sodium carbonate, and ammonia water; and the coupling agent is any one of A171 and A174.

[0028] In the scheme of the present invention, the oxidant described in component (5) can be one or more of ammonium persulfate, sodium persulfate, tert-butyl hydroperoxide, and hydrogen peroxide;

[0029] In the scheme of the present invention, the reducing agent described in component (6) can be one or more of sodium pyrosulfite, isoascorbic acid, hydrosulfite, bleaching powder, and FF6M;

[0030] In the scheme of the present invention, the post-addition auxiliary agent described in component (7) can be at least any one of an associative thickener, a neutralizer, a defoaming agent, and a preservative commonly used in emulsion polymerization.

[0031] On the other hand, a method for preparing an acrylic emulsion for tile adhesive comprises the following steps:

[0032] (1) mixing deionized water, a first part of emulsifier, a first part of hard monomer, a first part of soft monomer, and a chain transfer agent to obtain a pre-emulsion I; mixing deionized water, a second part of emulsifier, and a second part of soft monomer to obtain a pre-emulsion II;

[0033] (2) dividing the pre-emulsion I obtained in step (1) into two parts, the first part is placed in the bottom of the kettle, and the second part is used for dropwise addition;

[0034] (3) adding deionized water into the reaction kettle, heating it to 65-95° C., and adding the first part of the emulsifier and the first part of the pre-emulsion I into the bottom of the kettle;

[0035] (4) At 65-95° C., add part of the oxidant to the reactor. After 1-15 minutes, add the second part of the pre-emulsion I and the oxidant to the reactor. The total adding time is 100-180 minutes. When 75%-95% of the pre-emulsion I is added, stop adding. Add the second part of the hard monomer and the coupling agent to the remaining pre-emulsion I. After mixing for 5-20 minutes, continue adding until all the pre-emulsion I is added to the reactor.

[0036] (5) Keep warm for 5-30 min, then add pre-emulsion II and oxidant to the reaction kettle at 65-95°C for a total time of 10-30 min;

[0037] (6) keeping the temperature for 30-60 min, cooling to 55-75° C., and simultaneously adding the post-treatment oxidant and reducing agent dropwise, preferably for 30-60 min;

[0038] (7) Keep warm for 10-30 minutes, add a neutralizing agent to the reaction kettle at 50-70°C, preferably for 5-30 minutes; then add an associative thickener, and finally cool to below 50°C, add an auxiliary agent, stir evenly, and filter the material.

[0039] In the scheme of the present invention, the pre-emulsion I in step (1) may comprise the following composition, calculated by the total mass of the pre-emulsion I:

[0040]

[0041] In the scheme of the present invention, wherein the pre-emulsion II in step (1) comprises the following composition, calculated by the total mass of the pre-emulsion II:

[0042] Soft monomer 10-100 parts by mass, preferably 20-70 parts by mass;

[0043] Emulsifier 0.1-3 parts by mass, preferably 0.5-2 parts by mass;

[0044] 1-50 parts by mass of water, preferably 5-40 parts by mass;

[0045] On the other hand, the aforementioned application of acrylic emulsion for tile adhesive.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The present invention improves the cohesion of the product by cleverly designing the ratio of soft and hard monomers in the core-shell structure, avoiding the problem that conventional adhesive-backed products cannot have both high initial adhesion and high bonding strength. At the same time, the product solves the problem that conventional products have a decreased response to thickeners under long-term storage conditions through particle structure design. By adjusting the amount of thickener used, the viscosity of the emulsion can be freely controlled to meet the needs of different construction sites. DETAILED DESCRIPTION

[0048] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0050] An acrylic emulsion for tile adhesive, comprising the following components in parts by weight:

[0051]

[0052]

[0053] The pre-emulsion additive includes at least one of a chain transfer agent, a buffer, and a coupling agent. The post-addition additive includes at least one of an associative thickener, a neutralizer, a defoamer, and a preservative commonly used in emulsion polymerization.

[0054] In a specific embodiment, the acrylic emulsion for tile adhesive comprises the following components in parts by weight:

[0055] 60-120 parts by mass of hard monomer (e.g., 60 parts by mass, 65 parts by mass, 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass, 95 parts by mass, 100 parts by mass, 105 parts by mass, 110 parts by mass, 115 parts by mass, 120 parts by mass, etc.), preferably 80-100 parts by mass;

[0056] 300-450 parts by mass of soft monomer (e.g., 300 parts by mass, 310 parts by mass, 320 parts by mass, 330 parts by mass, 340 parts by mass, 350 parts by mass, 360 parts by mass, 370 parts by mass, 380 parts by mass, 390 parts by mass, 400 parts by mass, 410 parts by mass, 420 parts by mass, 430 parts by mass, 440 parts by mass, 450 parts by mass, etc.), preferably 350-420 parts by mass;

[0057] 5-20 parts by mass of emulsifier (e.g., 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, 9 parts by mass, 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, 15 parts by mass, 16 parts by mass, 17 parts by mass, 18 parts by mass, 19 parts by mass, 20 parts by mass, etc.), preferably 7-18 parts by mass;

[0058] Chain transfer agent 0.1-1 mass part (for example, 0.1 mass part, 0.2 mass part, 0.3 mass part, 0.4 mass part, 0.5 mass part, 0.6 mass part, 0.7 mass part, 0.8 mass part, 0.9 mass part, 1 mass part, etc.), preferably 0.2-0.8 mass part;

[0059] 0.5-2 parts by mass of coupling agent (e.g., 0.5 parts by mass, 0.6 parts by mass, 0.7 parts by mass, 0.8 parts by mass, 0.9 parts by mass, 1.0 parts by mass, 1.1 parts by mass, 1.2 parts by mass, 1.3 parts by mass, 1.4 parts by mass, 1.5 parts by mass, 1.6 parts by mass, 1.7 parts by mass, 1.8 parts by mass, 1.9 parts by mass, 2 parts by mass, etc.), preferably 0.7-1.8 parts by mass;

[0060] 2-8 parts by mass of an oxidant (e.g., 2 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, etc.), preferably 3-7 parts by mass;

[0061] 0.4-2 parts by mass of reducing agent (e.g., 0.4 parts by mass, 0.5 parts by mass, 0.6 parts by mass, 0.7 parts by mass, 0.8 parts by mass, 0.9 parts by mass, 1.0 parts by mass, 1.1 parts by mass, 1.2 parts by mass, 1.3 parts by mass, 1.4 parts by mass, 1.5 parts by mass, 1.6 parts by mass, 1.7 parts by mass, 1.8 parts by mass, 1.9 parts by mass, 2 parts by mass, etc.), preferably 0.5-1.5 parts by mass;

[0062] 3-7 parts by mass of a neutralizer (e.g., 3 parts by mass, 3.5 parts by mass, 4 parts by mass, 4.5 parts by mass, 5 parts by mass, 5.5 parts by mass, 6 parts by mass, 6.5 parts by mass, 7 parts by mass, etc.), preferably 4-6 parts by mass;

[0063] 0-3 parts by mass of an associative thickener (e.g., 0 parts by mass, 0.5 parts by mass, 1 parts by mass, 1.5 parts by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, etc.), preferably 0.5-2.5 parts by mass;

[0064] 0.1-1 mass part of defoaming agent (for example, 0.1 mass part, 0.2 mass part, 0.3 mass part, 0.4 mass part, 0.5 mass part, 0.6 mass part, 0.7 mass part, 0.8 mass part, 0.9 mass part, 1 mass part, etc.), preferably 0.2-0.8 mass part;

[0065] 3-7 parts by mass of preservative (e.g., 3 parts by mass, 3.5 parts by mass, 4 parts by mass, 4.5 parts by mass, 5 parts by mass, 5.5 parts by mass, 6 parts by mass, 6.5 parts by mass, 7 parts by mass, etc.), preferably 3.5-6.5 parts by mass;

[0066] Water 400-600 parts by mass (e.g., 400 parts by mass, 420 parts by mass, 440 parts by mass, 460 parts by mass, 480 parts by mass, 500 parts by mass, 520 parts by mass, 540 parts by mass, 560 parts by mass, 580 parts by mass, 600 parts by mass, etc.), preferably 450-550 parts by mass

[0067] In the core-shell latex particles of the present invention, the core layer and the shell layer account for 65%-95% and 5%-35% of the total mass of the polymer respectively (for example, core layer 65% shell layer 35%, core layer 75% shell layer 25%, core layer 85% shell layer 15%, core layer 95% shell layer 5%, etc.).

[0068] The acrylic emulsion for tile adhesive can be prepared by the conventional method of the present invention without any particular limitation, for example, by the following method, but not limited thereto.

[0069] A method for preparing acrylic emulsion for tile adhesive comprises the following steps:

[0070] (1) mixing deionized water, a first part of emulsifier, a first part of hard monomer, a first part of soft monomer, and a chain transfer agent to obtain a pre-emulsion I; mixing deionized water, a second part of emulsifier, and a second part of soft monomer to obtain a pre-emulsion II;

[0071] (2) dividing the pre-emulsion I obtained in step (1) into two parts, the first part is placed in the bottom of the kettle, and the second part is used for dropwise addition;

[0072] (3) Deionized water is added to the reaction kettle, the temperature is raised to 65-95° C., and the emulsifier and the first part of pre-emulsion I are added to the bottom of the kettle;

[0073] (4) adding part of the oxidant solution to the reactor at 65-95° C., and after 1-15 minutes, adding the second part of the pre-emulsion I and the oxidant solution to the reactor dropwise for a total time of 100-180 minutes. When 75%-95% of the pre-emulsion I has been added, stop adding dropwise, and add the second part of the hard monomer and the coupling agent to the remaining pre-emulsion I. After mixing for 5-20 minutes, continue adding dropwise until all the pre-emulsion I has been added to the reactor;

[0074] (5) Keep warm for 5-30 min, then add pre-emulsion II and oxidant to the reaction kettle at 65-95°C for a total time of 10-30 min;

[0075] (6) keeping the temperature for 30-60 min, cooling to 55-75° C., and simultaneously adding the post-treatment oxidant and reducing agent dropwise, preferably for 30-60 min;

[0076] (7) Keep warm for 10-30 minutes, add a neutralizing agent to the reaction kettle at 50-70°C, preferably for 5-30 minutes; then add an associative thickener, and finally cool to below 50°C, add an auxiliary agent, stir evenly, and filter the material.

[0077] In step (1) of the present invention, the emulsifier is one or more of COPS-1, sodium sulfate of tridecanol polyoxyethylene ether, sodium salt of sulfonated diphenyl ether tetrapropylene derivative, polyoxyethylene polystyrene phenol ether, sodium allyl ether hydroxypropyl sulfonate, and sodium p-styrene sulfonate. Preferably, the emulsifier accounts for 1-3% of the total monomer weight, wherein the total monomer weight is the sum of the weights of the hard monomer and the soft monomer.

[0078] In the present invention, the emulsifier is added in three parts, one part as the bottom liquid, one part in the pre-emulsion I, and one part in the pre-emulsion II, and the three parts add up to 5-20 parts by mass. In fact, there is no particular restriction on the proportion of these three parts. For example, in this step, the amount of the bottom emulsifier is 1-8 parts by mass, such as 1 part by mass, 2 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, etc., preferably 2-6 parts by mass. Wherein, the pre-emulsion I is divided into two parts, and the proportion of the two parts is not particularly limited. It can be referred to the usual means in the art, for example, the first part accounts for 3%-5% of the total amount and is put into the bottom of the kettle, and the second part accounts for 95%-97% of the total amount for dropwise addition.

[0079] In step (4) of the present invention, the oxidant is one or more of ammonium persulfate or sodium persulfate, tert-butyl hydroperoxide, and hydrogen peroxide, preferably ammonium persulfate or sodium persulfate. In this step, the amount of the oxidant is, for example, 1-6 parts by mass, such as 1 part by mass, 2 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, etc., preferably 3-7 parts by mass, wherein the ratio of the oxidant pre-added to the reactor and the oxidant added dropwise to the reactor is not particularly limited, such as an even distribution of the two parts. Among them, the oxidant pre-added to the reactor and the oxidant added dropwise to the reactor may be the same or different, preferably the same oxidant. According to conventional operations in the art, relatively more water may be appropriately added to facilitate the dropwise addition of the oxidant added dropwise to the reactor, which is a conventional operation in the art.

[0080] In step (4) of the present invention, the second part of the hard monomer is one or both of methacrylic acid and acrylic acid, and the coupling agent is one or both of silane coupling agents A171 and A174. Preferably, the second part of the hard monomer accounts for 0.2-1% of the total monomer weight, and the coupling agent accounts for 0.1%-0.5% of the total monomer weight. The total monomer weight is the sum of the weights of the hard monomer and the soft monomer.

[0081] The monomers in the present invention are added in three parts, one part in pre-emulsion I, one part inserted into pre-emulsion I after 75%-95% of pre-emulsion I is added dropwise, and one part in pre-emulsion II. Preferably, the monomers in pre-emulsion I account for 60%-80% of the total monomers, the inserted monomers account for 5%-10% of the total monomers, and the monomers in pre-emulsion II account for 10%-20% of the total monomers. The total monomer weight is the sum of the weights of the hard monomers and the soft monomers.

[0082] The pre-emulsion I in step (1) of the present invention comprises the following composition, calculated by the total mass of the pre-emulsion I:

[0083] 60-120 parts by mass of hard monomer, preferably 80-100 parts by mass;

[0084] 300-450 parts by mass of soft monomer, preferably 350-420 parts by mass;

[0085] Emulsifier 5-20 parts by mass, preferably 7-18 parts by mass;

[0086] 0.5-5 parts by mass, preferably 1-3 parts by mass, of pre-emulsion auxiliary agent;

[0087] 100-300 parts by mass of water, preferably 150-250 parts by mass;

[0088] Wherein, the pre-emulsion additives at least include a chain transfer agent and a coupling agent.

[0089] The preparation method of the pre-emulsion I is not particularly limited, and for example comprises the following steps: adding water, emulsifier, soft monomer, hard monomer, and pre-emulsion auxiliary agent into the pre-emulsification kettle 1, and stirring at high speed for 10-30 minutes.

[0090] The emulsifier in the pre-emulsion I is one or more of COPS-1, sodium sulfate of tridecanol polyoxyethylene ether, sodium salt of sulfonated diphenyl ether tetrapropylene derivative, polyoxyethylene polystyrene phenol ether, sodium allyl ether hydroxypropyl sulfonate, and sodium p-styrene sulfonate. Preferably, the emulsifier accounts for 1-3% of the total monomer weight. The total monomer weight is the sum of the weights of the hard monomer and the soft monomer. The amount of the emulsifier is 4-12 parts by mass, such as 4 parts by mass, 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, 9 parts by mass, 10 parts by mass, 11 parts by mass, 12 parts by mass, etc., preferably 5-10 parts by mass.

[0091] The hard monomer in the pre-emulsion I includes any one or more combinations of butyl methacrylate, acrylamide, methyl methacrylate, styrene, acrylic acid, and methacrylic acid. Preferably, the hard monomer is selected from a combination of acid monomers containing acrylic acid and / or methacrylic acid; more preferably, the acid monomer accounts for 2-8% of the total monomer weight. The amount of hard monomer added is 50-100 parts by mass (e.g., 50 parts by mass, 55 parts by mass, 60 parts by mass, 65 parts by mass, 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass, 95 parts by mass, 100 parts by mass, etc.), preferably 60-80 parts by mass.

[0092] The soft monomer in the pre-emulsion I includes any one or more of allyl methacrylate, isooctyl acrylate, butyl acrylate, and ethyl acrylate, and the soft monomer is added in an amount of 250-400 parts by mass (e.g., 250 parts by mass, 260 parts by mass, 270 parts by mass, 280 parts by mass, 290 parts by mass, 300 parts by mass, 310 parts by mass, 320 parts by mass, 330 parts by mass, 340 parts by mass, 350 parts by mass, 360 parts by mass, 370 parts by mass, 380 parts by mass, 390 parts by mass, 400 parts by mass, etc.), preferably 280-350 parts by mass.

[0093] The pre-emulsion auxiliary agent in the pre-emulsion I comprises at least any one of a chain transfer agent, a buffer, and a coupling agent; preferably, the chain transfer agent is any one of n-dodecyl mercaptan and mercaptobutyl ester, the buffer is any one of sodium bicarbonate, sodium carbonate, and ammonia water, and the coupling agent is any one of A171 and A174. The addition amount of the pre-emulsion auxiliary agent is 0.1-1 mass parts (e.g., 0.1 mass parts, 0.2 mass parts, 0.3 mass parts, 0.4 mass parts, 0.5 mass parts, 0.6 mass parts, 0.7 mass parts, 0.8 mass parts, 0.9 mass parts, 1 mass parts), preferably 0.2-0.8 mass parts.

[0094] The pre-emulsion II in step (1) of the present invention comprises the following composition, calculated by the total mass of the pre-emulsion II:

[0095] Soft monomer 10-100 parts by mass, preferably 20-70 parts by mass;

[0096] Emulsifier 0.1-3 parts by mass, preferably 0.5-2 parts by mass;

[0097] 1-50 parts by mass of water, preferably 5-40 parts by mass;

[0098] The preparation method of the pre-emulsion II is not particularly limited, and for example comprises the following steps: adding water, emulsifier, and soft monomer into the pre-emulsification kettle 2, and stirring at high speed for 10-30 minutes.

[0099] The emulsifier in the pre-emulsion II is one or more of COPS-1, sodium sulfate of tridecanol polyoxyethylene ether, sodium salt of sulfonated diphenyl ether tetrapropylene derivative, polyoxyethylene polystyrene phenol ether, sodium allyl ether hydroxypropyl sulfonate, and sodium p-styrene sulfonate. Preferably, the emulsifier accounts for 0.1-0.5% of the total monomer weight. The total monomer weight is the sum of the weights of the hard monomer and the soft monomer. The amount of the emulsifier is 0.4-2.4 parts by weight (e.g., 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, etc.)

[0100] The soft monomer in the pre-emulsion II includes any one or more of allyl methacrylate, isooctyl acrylate, butyl acrylate, and ethyl acrylate, and the added amount is 30-60 parts by mass (for example, 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, 50 parts by mass, 55 parts by mass, 60 parts by mass, etc.), preferably 35-55 parts by mass.

[0101] In step (6) of the present invention, the post-treatment oxidant is 1-3 parts by mass, for example, 1 part by mass, 2 parts by mass, 3 parts by mass, etc., preferably 2 parts by mass. The post-treatment oxidant is preferably tert-butyl hydroperoxide, which is mainly used to remove odors in the product. This is a conventional operation in the art.

[0102] In step (6) of the present invention, the amount of the post-treatment reducing agent is 0.4-2 parts by mass, for example, 0.4 parts by mass, 0.5 parts by mass, 0.6 parts by mass, 0.7 parts by mass, 0.8 parts by mass, 0.9 parts by mass, 1.0 parts by mass, 1.1 parts by mass, 1.2 parts by mass, 1.3 parts by mass, 1.4 parts by mass, 1.5 parts by mass, 1.6 parts by mass, 1.7 parts by mass, 1.8 parts by mass, 1.9 parts by mass, 2 parts by mass, etc., preferably 0.5-1.5 parts by mass, and the reducing agent is one or more of sodium metabisulfite, isoascorbic acid, hydrosulfite, bleaching powder, and FF6, preferably ascorbic acid.

[0103] In step (7) of the present invention, the neutralizing agent is preferably ethanolamine, dimethylethanolamine and / or NaOH solution, and the amount used is 3-7 parts by mass, for example, 3 parts by mass, 3.5 parts by mass, 4 parts by mass, 4.5 parts by mass, 5 parts by mass, 5.5 parts by mass, 6 parts by mass, 6.5 parts by mass, 7 parts by mass, etc., preferably 4-6 parts by mass.

[0104] In step (7) of the present invention, the associative thickener is preferably U604 and / or U515, and the amount used is 0-3 parts by weight, such as 0 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, etc., preferably 0.5-2.5 parts by weight;

[0105] In step (7) of the present invention, the defoaming agent is preferably Evonik Degussa Tego-825, Tego-1488 and / or 2410, and the amount used is 0.1-1 mass parts, for example, 0.1 mass parts, 0.2 mass parts, 0.3 mass parts, 0.4 mass parts, 0.5 mass parts, 0.6 mass parts, 0.7 mass parts, 0.8 mass parts, 0.9 mass parts, 1 mass parts, etc., preferably 0.2-0.8 mass parts.

[0106] In step (7) of the present invention, the preservative is preferably an isothiazolinone MIT preservative, and the amount used is 1-4 parts by mass, for example, 1 part by mass, 1.5 parts by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, 3.5 parts by mass, 4 parts by mass, etc., preferably 1.5-3.5 parts by mass.

[0107] The present invention improves the cohesion of the product by cleverly designing the ratio of soft and hard monomers in the core-shell structure, avoiding the problem that conventional adhesive products cannot have both high initial adhesion and high bonding strength. At the same time, the product solves the problem that conventional products have a decreased response to thickeners under long-term storage conditions through particle structure design. By adjusting the amount of thickener, the viscosity of the emulsion can be freely adjusted to meet the needs of different construction sites. The relevant explanation is as follows:

[0108] First, a chain transfer agent needs to be added to the pre-emulsion I to reduce the molecular chains inside the latex particles and improve the initial viscosity of the product;

[0109] Secondly, the acrylic emulsion of the present invention is divided into two parts, a core and a shell, through molecular structure design, wherein the core layer has more hard monomers and the shell layer has more soft monomers, so as to ensure that the latex particles have a structure of "soft outside and hard inside", and a large number of acidic hard monomers are inserted into the surface of the core layer to ensure that the molecular chain has high hydrophilicity. By controlling the types, proportions and amounts of monomers in the core layer and the shell layer polymers, the product is given better initial viscosity and sufficient cohesive force while maintaining the stability of the emulsion.

[0110] Thirdly, the acrylic emulsion of the present invention is neutralized by high temperature neutralization after polymerization. At room temperature, the acidic segments on the surface of the core layer are buried under the shell layer. If the acidic segments in the core layer are not completely neutralized in advance by high temperature neutralization, the hydrophilic segments will slowly extend to the surface of the shell layer over time, occupying the hydrophobic sites on the surface of the shell layer, resulting in unstable product viscosity and viscosity reduction. High temperature neutralization can make the hydrophilic and hydrophobic groups on the surface of the latex particles reach a stable state in advance, thereby ensuring the viscosity stability of the emulsion.

[0111] Finally, after the high-temperature neutralization of the acrylic emulsion of the present invention, an associative thickener is added near the heat storage temperature. The high temperature helps the thickener to be quickly and evenly dispersed in the emulsion. The hydrophobic end of the thickener associates with the hydrophobic end of the surface of the expanded polymer particles to play a thickening role. Since the high-temperature neutralization in advance ensures the stable state of the hydrophilic and hydrophobic groups on the surface of the latex particles, the viscosity of the emulsion can be freely controlled by adjusting the amount of the thickener to meet the needs of different construction sites.

[0112] The acrylic ester emulsion of the present invention adopts a pre-emulsification semi-continuous dripping process, which can effectively improve the polymerization stability and enable the chemical reaction to proceed under relatively mild conditions.

[0113] In summary, the present invention adopts an ingenious overall formula design, the obtained emulsion polymerization stage is stable, and the product viscosity can be adjusted according to actual needs. The tile backing glue prepared therefrom has high initial viscosity and high bonding strength, and can still maintain high bonding strength after soaking in water. It is non-toxic, environmentally friendly and easy to construct, and is an ideal bonding material.

[0114] The present invention is further described below by more specific examples, but does not constitute any limitation.

[0115] In the following examples, parts are by weight unless otherwise specified.

[0116] Main raw material sources

[0117] Table 1 Raw materials used to prepare acrylic emulsion for tile backing adhesive

[0118]

[0119]

[0120] Main test methods

[0121] (1) Water resistance: The tile adhesive emulsion provided in the examples and comparative examples was scraped onto a glass plate with a 100 μm wire rod, maintained in a constant temperature and humidity room for one day, and soaked in water for one day to test whether the varnish film could not be rubbed off by hand after being soaked in water.

[0122] (2) Initial adhesion: The tile adhesive emulsion provided in the examples and comparative examples was scraped onto a glass plate with a 100 μm wire rod. After curing in a constant temperature and humidity room for one day, the rolling distance of the ball on the adhesive surface of the glass plate was tested according to the rolling ball method according to GBT4852.

[0123] (3) Bonding strength: The tile adhesive emulsion provided in the examples and comparative examples was brushed onto the back of the vitrified tile with a size of 40*40 cm. After the emulsion was completely dry, it was pressed onto a small cement block and cured in a constant temperature and humidity room for 7 days. The bonding strength was then tested using a tensile tester.

[0124] (4) Bond strength after water treatment: The tile adhesive emulsion provided in the examples and comparative examples was brushed on the back of a vitrified tile with a size of 40*40 cm. After the emulsion was completely dry, it was pressed on a small piece of cement and cured in a constant temperature and humidity room for 7 days. It was soaked in water for 7 days, and the bond strength after water treatment was tested using a tensile tester.

[0125] (5) Emulsion viscosity: The emulsions for tile adhesive provided in the examples and comparative examples were tested for viscosity at room temperature (25° C.) using an RV rotary viscometer at 63# / 60 rpm.

[0126] (6) Emulsion hot storage viscosity: The tile adhesive emulsion provided in the examples and comparative examples was sealed with insulating tape, placed in a 50°C oven for hot storage for 14 days, and then taken out and allowed to cool to room temperature of 25°C. The emulsion viscosity was tested using an RV rotational viscometer at 63# / 60rpm.

[0127] Example 1: Emulsion 1-1

[0128] Preparation of pre-emulsion I: 130 parts of deionized water DIW, 6.3 parts of sodium alkyl sulfonate succinate DES-30, 1 part of sodium vinylbenzene sulfonate SSS, 55 parts of styrene ST, 175 parts of butyl acrylate BA, 3 parts of acrylic acid AA, 155 parts of isooctyl acrylate EHA, and 0.3 parts of butyl mercaptopropionate are placed in a pre-emulsification kettle I and stirred thoroughly.

[0129] Preparation of pre-emulsion II: 10 parts of deionized water DIW, 0.8 parts of sodium alkyl sulfonate succinate DES-30, 0.1 parts of sodium vinylbenzene sulfonate SSS, and 30 parts of butyl acrylate BA are placed in pre-emulsification kettle II and stirred thoroughly.

[0130] Preparation of fast-release oxidant solution: 5 parts of deionized water DIW, 0.8 parts of ammonium persulfate APS, put them in a fast-release oxidant tank and stir them thoroughly.

[0131] Preparation of dropwise oxidant solution: 20 parts of deionized water DIW, 0.5 parts of ammonium persulfate APS, put into the dropwise oxidant tank and stir thoroughly.

[0132] Add 300 parts of deionized water to the reactor, heat to 70°C, add 2 parts of allyl ether hydroxypropyl sulfonate COPS-1, 0.3 parts of alkyl succinate sulfonate sodium salt DES-30. Add 4% of pre-emulsion I solution and fast-release oxidant solution to the reactor, add the remaining part of pre-emulsion I solution and oxidant solution after 3 minutes, and control the reaction temperature at 70°C. When the pre-emulsion I solution is added to 75%, add 5 parts of methacrylic acid MAA and 1 part of A174 to pre-emulsion I, stir well and continue to add pre-emulsion I solution until all the pre-emulsion I solution is added, and the addition time is 120 minutes. After keeping warm for 10 minutes, add pre-emulsion II solution and the remaining part of the oxidant solution to the reactor until the addition is completed, and the addition time is 20 minutes. After keeping warm for 30 minutes, the temperature of the reactor was lowered to 60°C, and 1.8 parts of tert-butyl hydroperoxide TBHP dissolved in 10 parts of deionized water DIW and 0.6 parts of isoascorbic acid IAA dissolved in 10 parts of deionized water DIW were added dropwise for 40 minutes. After keeping warm for 30 minutes, 4 parts of MEA were added at 55°C for neutralization. The temperature was lowered to 50°C, 2 parts of U604 were added, and the mixture was stirred for 20 minutes. Then, 0.4 parts of defoamer Tego-825 and 1.9 parts of preservative Kordek MLX were added, and the mixture was stirred for 30 minutes to obtain emulsion 1-1.

[0133] Example 2: Emulsion 1-2

[0134] Preparation of pre-emulsion I: 160 parts of deionized water DIW, 8.5 parts of sodium alkyl sulfonate succinate DES-30, 1.2 parts of sodium vinylbenzene sulfonate SSS, 75 parts of styrene ST, 185 parts of butyl acrylate BA, 4 parts of acrylic acid AA, 135 parts of isooctyl acrylate EHA, and 0.4 parts of butyl mercaptopropionate are placed in a pre-emulsification kettle I and stirred thoroughly.

[0135] Preparation of pre-emulsion II: 13.5 parts of deionized water DIW, 1 part of sodium salt of alkyl succinate sulfonate DES-30, 0.2 parts of sodium vinylbenzene sulfonate SSS, and 45 parts of butyl acrylate BA are placed in pre-emulsification kettle II and stirred thoroughly.

[0136] Preparation of fast-release oxidant solution: 6 parts of deionized water DIW, 1 part of ammonium persulfate APS, put them in a fast-release oxidant tank and stir them thoroughly.

[0137] Preparation of dropwise oxidant solution: 30 parts of deionized water DIW, 0.8 parts of ammonium persulfate APS, placed in the dropwise oxidant tank and stirred thoroughly.

[0138] Add 250 parts of deionized water to the reactor, heat to 80°C, add 2.5 parts of allyl ether hydroxypropyl sulfonate COPS-1, 0.5 parts of alkyl succinate sulfonate sodium salt DES-30. Add 4% of the pre-emulsion I solution and the fast-release oxidant solution to the reactor, and add the remaining part of the pre-emulsion I solution and the oxidant solution after 8 minutes, and control the reaction temperature at 80°C. When the pre-emulsion I solution is added to 90%, add 6 parts of methacrylic acid MAA and 2 parts of A174 to the pre-emulsion I, stir well, and continue to add the pre-emulsion I solution until the pre-emulsion I solution is completely added, and the addition time is 150 minutes. After keeping warm for 10 minutes, add the pre-emulsion II solution and the remaining part of the oxidant solution to the reactor until the addition is completed, and the addition time is 30 minutes. After keeping warm for 30 minutes, the temperature of the reactor was lowered to 65°C, and 2 parts of tert-butyl hydroperoxide TBHP dissolved in 10 parts of deionized water DIW and 0.8 parts of isoascorbic acid IAA dissolved in 10 parts of deionized water DIW were added dropwise for 40 minutes. After keeping warm for 45 minutes, 5 parts of MEA were added at 65°C for neutralization. The temperature was lowered to 50°C, 3.5 parts of U604 were added, and the mixture was stirred for 20 minutes. Then, 0.6 parts of defoamer Tego-825 and 1.9 parts of preservative Kordek MLX were added, and the mixture was stirred for 30 minutes to obtain emulsion 1-2.

[0139] Example 3: Emulsion 1-3

[0140] Preparation of pre-emulsion I: 240 parts of deionized water DIW, 15 parts of sodium alkyl sulfonate succinate DES-30, 3 parts of sodium vinylbenzene sulfonate SSS, 105 parts of styrene ST, 210 parts of butyl acrylate BA, 5 parts of acrylic acid AA, 180 parts of isooctyl acrylate EHA, and 0.4 parts of butyl mercaptopropionate are placed in a pre-emulsification kettle I and stirred thoroughly.

[0141] Preparation of pre-emulsion II: 30 parts of deionized water DIW, 1.5 parts of sodium alkyl sulfonate succinate DES-30, 0.3 parts of sodium vinylbenzene sulfonate SSS, and 50 parts of butyl acrylate BA are placed in pre-emulsification kettle II and stirred thoroughly.

[0142] Preparation of fast-release oxidant solution: 10 parts of deionized water DIW, 2 parts of ammonium persulfate APS, put them in a fast-release oxidant tank and stir them thoroughly.

[0143] Preparation of dropwise oxidant solution: 35 parts of deionized water DIW, 1.8 parts of ammonium persulfate APS, placed in the dropwise oxidant tank and stirred thoroughly.

[0144] Add 230 parts of deionized water to the reactor, heat to 85°C, add 2 parts of allyl ether hydroxypropyl sulfonate COPS-1, 0.4 parts of alkyl succinate sulfonate sodium salt DES-30. Add 4.5% of the pre-emulsion I solution and the fast-release oxidant solution to the reactor, and add the remaining part of the pre-emulsion I solution and the oxidant solution after 15 minutes, and control the reaction temperature at 85°C. When the pre-emulsion I solution is added to 80%, add 6 parts of methacrylic acid MAA and 2 parts of A174 to the pre-emulsion I, stir well, and continue to add the pre-emulsion I solution until the pre-emulsion I solution is completely added, and the addition time is 170 minutes. After keeping warm for 10 minutes, add the pre-emulsion II solution and the remaining part of the oxidant solution to the reactor until the addition is completed, and the addition time is 20 minutes. After 60 minutes of heat preservation, the contents of the reactor were cooled to 70°C, and 3 parts of tert-butyl hydroperoxide TBHP dissolved in 20 parts of deionized water DIW and 1.2 parts of isoascorbic acid IAA dissolved in 15 parts of deionized water DIW were added dropwise for 40 minutes. After 60 minutes of heat preservation, 4.5 parts of MEA were added at 70°C for neutralization. The temperature was lowered to 50°C, 4 parts of U604 were added, and the mixture was stirred for 20 minutes. Then, 1 part of defoamer Tego-825 and 3 parts of preservative Kordek MLX were added, and the mixture was stirred for 30 minutes to obtain emulsion 1-3.

[0145] Example 4: Emulsion 1-4

[0146] Preparation of pre-emulsion I: 200 parts of deionized water DIW, 8 parts of sodium salt of alkyl sulfonate succinate DES-30, 1.5 parts of sodium vinylbenzene sulfonate SSS, 80 parts of styrene ST, 200 parts of butyl acrylate BA, 10 parts of acrylic acid AA, 180 parts of isooctyl acrylate EHA, and 0.5 parts of butyl mercaptopropionate are placed in a pre-emulsification kettle I and stirred thoroughly.

[0147] Preparation of pre-emulsion II: 25 parts of deionized water DIW, 1.2 parts of sodium alkyl sulfonate succinate DES-30, 0.3 parts of sodium vinylbenzene sulfonate SSS, and 50 parts of butyl acrylate BA are placed in pre-emulsification kettle II and stirred thoroughly.

[0148] Preparation of fast-release oxidant solution: 10 parts of deionized water DIW, 2 parts of ammonium persulfate APS, put them in a fast-release oxidant tank and stir them thoroughly.

[0149] Preparation of dropwise oxidant solution: 35 parts of deionized water DIW, 1 part of ammonium persulfate APS, put into the dropwise oxidant tank and stir thoroughly.

[0150] Add 250 parts of deionized water to the reactor, heat to 90°C, add 2 parts of allyl ether hydroxypropyl sulfonate COPS-1, 0.4 parts of alkyl succinate sulfonate sodium salt DES-30. Add 4.5% of pre-emulsion I solution and fast-release oxidant solution to the reactor, add the remaining part of pre-emulsion I solution and oxidant solution after 8 minutes, and control the reaction temperature at 90°C. When the pre-emulsion I solution is added to 80%, add 7 parts of methacrylic acid MAA and 1.5 parts of A174 to pre-emulsion I, stir well and continue to add pre-emulsion I solution until all the pre-emulsion I solution is added, and the addition time is 160 minutes. After keeping warm for 10 minutes, add pre-emulsion II solution and the remaining part of the oxidant solution to the reactor until the addition is completed, and the addition time is 20 minutes. After 60 minutes of heat preservation, the contents of the reactor were cooled to 70°C, and 3 parts of tert-butyl hydroperoxide TBHP dissolved in 20 parts of deionized water DIW and 1.2 parts of isoascorbic acid IAA dissolved in 15 parts of deionized water DIW were added dropwise for 40 minutes. After 60 minutes of heat preservation, 4.5 parts of MEA were added at 70°C for neutralization. The temperature was lowered to 50°C, 4 parts of U604 were added, and the mixture was stirred for 20 minutes. Then, 1 part of defoamer Tego-825 and 3 parts of preservative Kordek MLX were added, and the mixture was stirred for 30 minutes to obtain emulsion 1-3.

[0151] Comparative Example 1: Emulsion 2-1

[0152] The difference from Example 1 is that the amount of butyl mercaptopropionate in the pre-emulsion auxiliary agent is increased from 0.3 parts to 2 parts, and the other components and the emulsion preparation method are exactly the same as those in Example 1.

[0153] Comparative Example 2: Emulsion 2-2

[0154] The difference from Example 2 is that no A174 is added to the core layer, while 2 parts of A174 are added to the shell layer. The other components and the emulsion preparation method are exactly the same as those in Example 2.

[0155] Comparative Example 3: Emulsion 2-3

[0156] The difference from Example 3 is that the neutralization temperature is reduced from 70° C. to 40° C., and the other components and the emulsion preparation method are exactly the same as those in Example 3.

[0157] Comparative Example 4: Emulsion 2-4

[0158] The difference from Example 4 is that the amount of the neutralizing agent MEA for high-temperature neutralization is reduced from 6 parts to 4 parts, and the other components and the emulsion preparation method are exactly the same as those in Example 4.

[0159] The pH value of the tile adhesive emulsion provided in the embodiment and the comparative example is 7.5-9.0, and the solid content is about 45%. The emulsions of the embodiment and the comparative example are tested for performance, and the test results are shown in Table 2.

[0160] Table 2 Performance test

[0161]

[0162] As can be seen from Table 2, the emulsion for tile adhesive prepared by the embodiment of the present invention has high initial viscosity, excellent bonding strength, still maintains high bonding strength after water treatment, the varnish film has excellent water resistance, the emulsion viscosity can be freely adjusted, and the viscosity is stable after heat storage.

[0163] Compared with the reaction system of the embodiment of the present invention, the ratio of chain transfer agent in the pre-emulsion additive is greatly increased in Comparative Example 1, the core layer in the raw material components of Comparative Example 2 is a coupling agent A174, low temperature neutralization is used in Comparative Example 3, and the amount of neutralizer MEA is reduced in Comparative Example 4. As shown in Table 2, the initial viscosity of Comparative Example 1 is improved compared with Example 1, but the bonding strength is greatly reduced; the strength of Comparative Example 2 is improved compared with Example 2, but the water resistance and initial viscosity are greatly reduced; the viscosity stability of the emulsion in Comparative Example 3 is reduced compared with Example 3; the viscosity stability of the emulsion in Comparative Example 4 is reduced compared with Example 4, and it is impossible to take into account the initial viscosity, the bonding strength before and after treatment, the viscosity of the emulsion and its stability, and the water resistance of the paint film. It is easy to understand that the above embodiments are only examples for clear explanation, and it does not mean that the present invention is limited to this. For ordinary technicians in the field, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to exhaust all the embodiments here. And the obvious changes or changes derived from this are still within the scope of protection of the invention.

Claims

1. An acrylic emulsion for tile adhesive, characterized in that: The material is prepared by core-shell emulsion polymerization of the following raw materials by weight: The core layer and shell layer of the core-shell latex particles account for 65%-95% and 5%-35% of the total mass of the polymer respectively.

2. The acrylic emulsion for tile adhesive according to claim 1, characterized in that: The hard monomer is selected from any one or more combinations of butyl methacrylate, acrylamide, methyl methacrylate, styrene, acrylic acid, and methacrylic acid; preferably, the hard monomer is selected from a combination of acid monomers of acrylic acid and / or methacrylic acid; more preferably, the acid monomer accounts for 2-8% of the total monomer weight.

3. The acrylic emulsion for tile adhesive according to claim 1, characterized in that: The soft monomer is selected from any one or more of allyl methacrylate, isooctyl acrylate, butyl acrylate, and ethyl acrylate.

4. The acrylic emulsion for tile adhesive according to claim 1, characterized in that: The emulsifier is any one or more combinations of COPS-1, sodium tridecyl alcohol polyoxyethylene ether sulfate, sodium salt of sulfonated diphenyl ether tetrapropylene derivative, polyoxyethylene polystyrene phenol ether, sodium allyl ether hydroxypropyl sulfonate, sodium dodecyl sulfate, and sodium p-styrene sulfonate.

5. The acrylic emulsion for tile adhesive according to claim 1, characterized in that: The pre-emulsion auxiliary agent includes at least any one of a chain transfer agent, a buffer, and a coupling agent; preferably, the chain transfer agent is any one of n-dodecyl mercaptan and butyl mercapto, the buffer is any one of sodium bicarbonate, sodium carbonate, and ammonia water, and the coupling agent is any one of A171 and A174.

6. The acrylic emulsion for tile adhesive according to claim 1, characterized in that: The oxidant is one or more of ammonium persulfate, sodium persulfate, tert-butyl hydroperoxide, and hydrogen peroxide; Preferably, the reducing agent is one or more of sodium pyrosulfite, isoascorbic acid, hydrosulfite, bleaching powder, and FF6M; Preferably, the post-added auxiliary agent includes at least any one of an associative thickener, a neutralizer, a defoamer, and a preservative commonly used in emulsion polymerization.

7. The method for preparing the acrylic emulsion for tile adhesive according to any one of claims 1 to 6, characterized in that: The steps include: (1) mixing deionized water, a first part of emulsifier, a first part of hard monomer, a first part of soft monomer, and a chain transfer agent to obtain a pre-emulsion I; mixing deionized water, a second part of emulsifier, and a second part of soft monomer to obtain a pre-emulsion II; (2) dividing the pre-emulsion I obtained in step (1) into two parts, placing the first part into the bottom of the kettle, and adding the second part dropwise; (3) adding deionized water to the reaction kettle, heating it to 65-95° C., and adding the first part of the emulsifier and the first part of the pre-emulsion I to the bottom of the kettle; (4) At 65-95° C., add part of the oxidant to the reactor. After 1-15 minutes, add the second part of the pre-emulsion I and the oxidant to the reactor dropwise. The total dropwise addition time is 100-180 minutes. When 75%-95% of the pre-emulsion I is added, stop adding. Add the second part of the hard monomer and the coupling agent to the remaining pre-emulsion I. After mixing for 5-20 minutes, continue adding until all the pre-emulsion I is added to the reactor. (5) Keep warm for 5-30 min, then add pre-emulsion II and oxidant to the reaction kettle at 65-95°C for a total time of 10-30 min; (6) keeping the temperature for 30-60 min, cooling to 55-75° C., and simultaneously adding the post-treatment oxidant and reducing agent dropwise, preferably for 30-60 min; (7) Keep warm for 10-30 minutes, add a neutralizing agent to the reaction kettle at 50-70°C, preferably for 5-30 minutes; then add an associative thickener, and finally cool to below 50°C, add an auxiliary agent, stir evenly, and filter the material.

8. The preparation method according to claim 7, characterized in that: The pre-emulsion I comprises the following composition, calculated by the total mass of the pre-emulsion I:

9. The preparation method according to claim 7, characterized in that: The pre-emulsion II comprises the following composition, calculated by the total mass of the pre-emulsion II: Soft monomer 10-100 parts by mass, preferably 20-70 parts by mass; Emulsifier 0.1-3 parts by mass, preferably 0.5-2 parts by mass; Water: 1-50 parts by mass, preferably 5-40 parts by mass.

10. Use of the acrylic ester emulsion for tile adhesive as claimed in any one of claims 1 to 6 or the acrylic ester emulsion for tile adhesive prepared by the preparation method as claimed in any one of claims 7 to 9 in tile adhesive.

Citation Information

Patent Citations

  • Environment-friendly tert-carbonic acid organic silicone-acrylic modified copolymer emulsion for ceramic tile back adhesive

    CN111154026A

  • Preparation method and application of acrylic acid high-initial-viscosity high-strength back adhesive emulsion

    CN114634592A

  • Core-shell structure acrylate emulsion, preparation method and applications thereof

    CN109929067A

  • Water-based acrylic contact adhesive emulsion, preparation method and application thereof

    CN119161528A

  • Core-shell latex with non-yellowing properties

    WO2020170272A1